Ingestion of multiple magnets in pediatrics: endoscopic or surgical emergency? - Martínez, Clara Isabel (2021)
Ingestion of foreign bodies is common in the pediatric population. Most foreign bodies have a benign behavior and are usually eliminated without generating greater morbidity and mortality. In relation to the intake of magnets, its frequency has increased to the point that it currently represents a public health problem in the pediatric population. The ingestion of a single magnet does not generate any risk, but the ingestion of 2 or more of these, or even of magnets and metals in succession is considered an emergency since they can attract each other and can cause serious symptoms of intestinal obstruction, bleeding, fistulas, perforation and even intestinal necrosis. We present 2 pediatric patients, who ingested multiple magnets, in these cases we highlight the variety in the clinical presentation, as well as the complications presented in relation to a late diagnosis.